25.78 Gbit/s data transmission over 2 km multi‐mode‐fibre with 850 and 910 nm single‐mode VCSELs and a commercial quad small form‐factor pluggable transceiver. Issue 12 (1st June 2018) - Ledentsov, N.; Agustin, M.; Chorchos, L.; Ledentsov, N. N.; Turkiewicz, J. P.
Abstract : Dispersion in the multimode fibres (MMF) limits the transmission distance of the modern data communication networks. The authors show that the use of single‐mode (SM) vertical cavity surface emitting lasers (VCSELs) in combination with the receiver module of a commercially available transceiver can increase the transmission distance to several kilometres. They report 25.78 Gbit/s error‐free transmission over 1800 m of multimode fibre with 850 nm and 1400 m with 910 nm SM VCSELs. Data transmission up to 2600 and 2400 m can be achieved with BER below 3.8×10 −3 forward error correction limit accordingly. The use of multiple wavelengths demonstrates the opportunity to increase the capacity of MMF links with shortwave wavelength division multiplexing.